Against whom Does Democracy Fight? - Kačerauskas, Tomas (Problemos, 2006)
The article deals with the place of war in democracy. The author raises three theses: 1) democracy and fight are inseparable, democracy gains its limits and identity only through a fight; 2) a fight is necessary for the formation of a living world and an individual within it; 3) external open fight is part of democracy’s culture of war. These theses are elaborated in the context of hermeneutics and phenomenology of culture. According to the author, politics is part of creation (culture) of living environment. This part gives the dynamics to the whole living world. The author’s theses are based on C. Schmitt’s concept of politics as war, J. Derrida’s and Ch. Mouffe’s concept of democracy-to-come, and also on Aristotle’s conception of the dynamical world. The author sets apart three types of democracy’s fight: the open internal, the closed external, and the closed internal fight. Connections among these three types are examined. Internal (not external) fight is treated as a factor of creativity.
Keywords: democracy; fight; limit; political body; and living world